HΛ3 and H‾Λ‾3 lifetime measurement in Pb–Pb collisions at sNN=5.02 TeV via two-body decay - S. Acharya; D. Adamová; S.P. Adhya; A. Adler; J. Adolfsson; M.M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; et al. (Physics Letters B, 2019)
An improved value for the lifetime of the (anti-)hypertriton has been obtained using the data sample of Pb–Pb collisions at sNN=5.02 TeV collected by the ALICE experiment at the LHC. The (anti-)hypertriton has been reconstructed via its charged two-body mesonic decay channel and the lifetime has been determined from an exponential fit to the dN/d(ct) spectrum. The measured value, τ=242−38+34 (stat.) ± 17 (syst.) ps, is compatible with representative theoretical predictions, thus contributing to the solution of the longstanding hypertriton lifetime puzzle.